2020
DOI: 10.1051/e3sconf/202017303008
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Window-Wall Ratio on Heating Energy Consumption of Rural House in Severe Cold Regions of China

Abstract: Rural houses in severe cold areas of China are mostly single-storey independent buildings with large shape coefficient. Compared with urban residential, it has larger contact area between envelope and outdoor environment of each household. Meanwhile, the heat transfer coefficient of window is usually greater than that of external wall and roof. The window-wall ratio is one of the important indicators affecting the energy consumption of rural house. This paper takes window-wall ratio as the main variable, build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Ozel and Ozel (2020) investigated the effect of WWR on the thermal performance of different wall materials and concluded that for the case of bare wall the wall material affected the glazed area, whereas in the case of the insulated wall, the effect was marginal. Shao et al (2020) used the Design builder software to determine the optimum value for WWR for rural house design considering other parameters such as building orientation and thermal performance among others. Their recommendation is that the effect of various factors should be considered in the design to determine the WWR of rural houses.…”
Section: Effect Of Window To Wall Ratiomentioning
confidence: 99%
“…Ozel and Ozel (2020) investigated the effect of WWR on the thermal performance of different wall materials and concluded that for the case of bare wall the wall material affected the glazed area, whereas in the case of the insulated wall, the effect was marginal. Shao et al (2020) used the Design builder software to determine the optimum value for WWR for rural house design considering other parameters such as building orientation and thermal performance among others. Their recommendation is that the effect of various factors should be considered in the design to determine the WWR of rural houses.…”
Section: Effect Of Window To Wall Ratiomentioning
confidence: 99%
“…Rural houses in this region are mainly constructed by local builders with few restrictions from building codes. The survey results indicate that only 28% of them have thermal insulation installed on external walls, and 2% of houses consider ground floor insulation [3]. Because of the poor envelope performance combined with the extremely low temperature in winter, these houses have a considerable level of heating demand.…”
Section: Introductionmentioning
confidence: 99%
“…Without access to district heating, the primary heating systems in these rural houses are Chinese Kangs (heated beds as living and sleeping platforms) and boilers with waterbased radiators, representing 99% and 51% of heating choices, respectively [3]. These traditional heating systems consume coal or biomass and have an efficiency of 30-50% [4,5].…”
Section: Introductionmentioning
confidence: 99%